Pengembangan hasil praktik kewirausahaan: Usaha keripik khacaww - Pranata, irwan Irwan (Maliki Interdisciplinary Journal, 2025)
Entrepreneurship is an effective learning tool to promote the spirit of enterprise, creativity, and management in students. This article will cover the development of a snack company called Khacaww chips. This was done by a group of students with the concept of Glasp with a distinctive spicy aroma. This product is designed as a light snack that fits the current culinary trend, aiming to be young consumers who like the extreme taste and uniqueness of its packaging. The production process takes place regardless of the processing of materials to packaging and marketing. This is mainly done digitally through social media. Calculating production costs, determining selling prices, and cash capital analysis (BEP) are important parts of this business management. The results of the practice show that the company can be further developed with strategies such as adding flavors, packaging quality, and expanding the market platform. This practice provides real experience in managing entrepreneurs from scratch and teaches the importance of teamwork, product innovation, and adaptation to market requirements. The Khacaww chips business is a real example of how simple ideas with excellent management can create promising and sustainable business opportunities.